Radio Absorption and Shielding of Electromagnetic Radiation by Polypyrroleand Magnetite-Based Textiles in the 3.9…8 GHz Frequency Range - A. E. Scherbakov (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. Composite materials based on electrically conductive polymers find application in various fields. However, the rather low mechanical strength of electrically conductive polymers require addition of other components to enhance their, e.g., mechanical properties. Another direction consists in the development of textile-based composite materials for shielding electromagnetic waves. Due to the low specific density and, respectively, low weight, as well as high absorption efficiency, such materials find application in the fields of human protection from electromagnetic radiation.Aim. Quantitative assessment and analysis of the radio-absorbing properties of two- and three-component textile composites, which emerge due to their electrically conductive and magnetic characteristics.Materials and methods. S parameters were measured using a Keysight N5232A vector circuit analyzer. Measurements carried out separately in two frequency ranges: 3.9…5.65 GHz and 5.65…8 GHz. Waveguides of a given cross section were used for the selected frequency ranges (3.9…5.65 GHz – 48 × 24 mm; 5.65…8 GHz – 35 × 15 mm). The experimental samples were composite materials based on non-woven textiles consisting of viscose and polyester fiber in a ratio of 60 and 40 wt %, respectively.Results. The S11 parameters characterizing wave reflection from the sample surface (Sr) (reflection) and the S12 parameters characterizing the sample permeability (St ) (transmittance) were determined. Data for single- and multilayered samples was obtained. The dielectric and magnetic permeability of the obtained materials was calculated.Conclusion. The studied materials showed a high degree of both shielding and absorption of electromagnetic radiation. Magnetite-based samples demonstrated largely shielding properties against electromagnetic radiation; polypyrrole-based samples were characterized by absorbing properties. The total absorption level of 6-mm thick polypyrrole-based samples was 90 %. The obtained electrophysical parameters can be used when designing and modeling of radio-absorbing products based on the studied materials.